FORMS OF SYNONYMS IN THE SEPATAH MALAY LANGUAGE OF SENGAH TEMILA SUBDISTRICT LANDAK REGENCY: A SEMANTIC STUDY - Dina Febiyanti; Yanti, Lili; Mulyani, Sri (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2025)
This study aims to describe the forms of synonyms in the Malay language of Desa Sepatah, located in the Sengah Temila District, Landak Regency, using a semantic approach. Synonyms in this language are divided into three main categories: absolute, propositional, and partial synonyms. Absolute synonyms refer to pairs of words that can replace each other in a sentence without changing the intended meaning, such as the pair pangan and ayong, which both mean ‘friend.’ Propositional synonyms describe pairs of words that have almost identical meanings but are used in specific contexts, such as gemok and bantet, which both mean ‘fat.’ Meanwhile, partial synonyms refer to pairs of words that cannot replace each other in the same sentence due to more specific differences in meaning, such as remok and rebok, which both mean ‘damaged.’ This study uses a qualitative descriptive method with data collection techniques through observation, active participation in conversations, and recorded conversations. The results show that the use of synonyms in the Malay language of Desa Sepatah is clearly categorized into these three types, in line with the intended meaning. Therefore, understanding synonyms is essential to enriching vocabulary and preserving regional languages as part of the local community's cultural identity.